THE EFFECT OF ENVIRONMENTAL POLLUTION ON THE QUALITY OF PUBLIC HEALTH - Andiko Nugraha Kusuma (Jurnal Ekonomi, 2022)
Environmental pollution is one of the most influential factors on the balance of ecosystems and human life. RI Law No. 32 of 2009 concerning environmental management article 1 paragraph 14 states that, environmental pollution is the entry or inclusion of living things, substances, energy and/or other components into the environment by human activities so that they exceed environmental quality standards. defined life. The implementation of human development is increasing, it turns out that it can contain the risk of environmental degradation and destruction, so that the basic structure and function of the ecosystem can also be damaged because of it. Any activity or activity carried out including industrial activities will certainly have an impact on the environment and public health at large. With the large influence of environmental quality on public health, it is very necessary to develop environmentally sound development. Basically, environmentally sound development is development that is able to bring people evenly to obtain their necessities of life (spiritual and material), including environmental quality that is suitable for habitation, so that people are not affected by diseases due to environmental pollution, and natural resources are increasingly fertile for the survival of the next generation. This paper will comprehensively describe the effect of environmental pollution (pollution of water, soil, air, and food) on public health